STEM-CP (Science, Technology, Engineering, Mathematics, and Contextual Problem) Based Colloid Textbook to Increase Creative Thinking Skill for Chemistry Learning in Senior High School - N Hasanah; Sutarto Sutarto; Nuriman Nuriman; A S Budiarso (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
The colloid is a chemistry subject matter which is closely related to our daily life. Most of the teachers apply colloidal learning in their classroom only by requiring the students to read and memorize. It gives fewer opportunities for the students to think creatively and they also lack understanding the benefits of learning colloidal subjects. This study aimed to apply Colloid textbooks based on STEM-Cp (Science, Technology, Engineering, Mathematics, and Contextual problems) to train creative thinking skills for chemistry learning in senior high school. This research used the Quasi Pretest-Posttest experiment without the control class. The research instrument used was a test of creative thinking skills. The effectiveness of textbook shown that each component of creative thinking, such as fluency, flexibility, elaboration and originality thinking gets a percentage of 89.20%, 86.31%, 80, 98%, 80.09% and N-gain score of students get value ≥ 0.7 which is 72.22% of students in the high category and 27.78% of students in the medium category.